Teknik Menyusui Berhubungan dengan Keberhasilan ASI Eksklusif - Bertalina, Bertalina Bertalina; Sri Wahyuni, Endang; Bela Martina, Keke (Journal of Dietetics Science, 2025)
Breast milk is the best nutrition for optimal growth and development in infants. It is essential for a child's growth and intelligence. Infants who are not exclusively breastfed until the first six months of life are at risk of developing infectious diseases such as severe diarrhea. This study was descriptive with a cross-sectional approach. The sample size was 38 respondents. The study was conducted in Bumi Waras Village, Bumi Waras District, Bandar Lampung City. Data collection took place in April 2024. Data analysis used chi square test. The results of the study showed that 10.5% of babies received exclusive breastfeeding. Mother who had low knowledge of exclusive breastfeeding was 63.2%, received rooming in care were 34.2%, carried out early breastfeeding initiation were 50%, found history difficulty in breastfeeding were 92.1%. Chi square test showed that there were no significant relationship between  exclusive breastfeeding and early breastfeeding initiation (p = 0.113), rooming in (p = 0.207), mothers' knowledge (p = 0.788). There was a significant relationship between breastfeeding techniques exclusive breastfeeding and exlusive breastfeeding (p = 0.02). The Community Health Center can provide education to pregnant women to choose health facilities that provide Rooming In and Early Breastfeeding Initiation (IMD). Health workers should provide education on exclusive breastfeeding and breastfeeding techniques to mothers from pregnancy through integrated health posts, pregnancy classes, and community health centers.